A MODEL FOR THE DEVELOPMENT OF SOCIALLY RESPONSIBLE LEADERSHIP IN UNDERGRADUATES IN XIAMEN, CHINA - ZHANG, CHONGYAN; ASAVISANU, POONPILAS (Scholar: Human Sciences, 2022)
There is an increasing need for leadership that values and promotes change and improvement for society in the 21st century. It is especially true for China which has experienced tremendous social and economic growth in many large cities. Higher education plays an important role in the development of such leadership. This research aimed to develop a model for developing socially responsible leadership for undergraduate students in Xiamen, China. This research was conducted using a sequential mixed-methods approach utilizing qualitative and quantitative methods. The study was based on the following objectives: 1) To determine the desired Confucian principles that form the basis of socially responsible behavior of Chinese students; 2) To determine the types of student leadership activities that can promote socially responsible leadership in students; 3) To identify the current type of student leadership activities that promote socially responsible leadership that are available in universities in Xiamen, China; 4) To determine if there is a relationship or a difference between the type of activity, frequency of participation and demographics of students and the level of socially responsible leadership of students in Xiamen, China; and finally, 5) To propose a model for the development of socially responsible leadership for students in Xiamen, China. The literature and interviews identified five core Confucian values: Benevolence, Righteousness, Manner, Wisdom, and Trustworthiness. Leadership activities included workshops, classroom, club, student organization, and games. Five hundred students from a representative university in Xiamen, China, were surveyed. A significant relationship was found among students’ demographics, participation frequency, leadership activities, and levels of socially responsible leadership. (four categories of leadership activities with p<.05 they were a significant relationship with socially responsible leadership) A final model was developed from the research findings and validated by experts.